Cálculo, ontología y metafísica: el proyecto ontoteológico de leibniz - Esquisabel, Oscar Miguel (2014)
This paper develops an outline of the close connection that, according to Leibniz’s view, obtains between ontology and logic to the extent that the latter can be conceived as a replacement for the former. At the same time, the leibnizian views on logic as ontology is interpreted in the context of the 17th Century discussion about the status and structure of metaphysics as a philosophical discipline.